2018
DOI: 10.1002/jum.14693
|View full text |Cite
|
Sign up to set email alerts
|

Scapular Upward Rotator Morphologic Characteristics in Individuals With and Without Forward Head Posture: A Case‐Control Study

Abstract: Forward head posture appears to be related to atrophy of the serratus anterior muscle, which may contribute to the development of shoulder problems. Further research is required to identify more about the association of forward head posture with the imbalance of shoulder girdle muscles and the impact of head posture on upper quadrant pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…A case control study revealed that FHP related to atrophy of serratus anterior muscle which contributes scapula and shoulder problems. 32 In our study, we excluded patients with shoulder problems, future studies should evaluate the effects of both head forward posture and SD on shoulder problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A case control study revealed that FHP related to atrophy of serratus anterior muscle which contributes scapula and shoulder problems. 32 In our study, we excluded patients with shoulder problems, future studies should evaluate the effects of both head forward posture and SD on shoulder problems.…”
Section: Discussionmentioning
confidence: 99%
“…Each division was given a raw score from 0 to 5 (0: best condition, 5: worst condition). The score can range from 0 to 50 and classifies individuals as having no disability (0-4), mild disability (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), moderate disability (15)(16)(17)(18)(19)(20)(21)(22)(23)(24), severe disability (25)(26)(27)(28)(29)(30)(31)(32)(33)(34) and complete disability (≥35). The validity and cross-cultural reliability of NDI in Turkish version done by Telci et al in 2009.…”
Section: Neck Disability Indexmentioning
confidence: 99%
“…La anteposición de cabeza y cuello, es una alteración postural que se caracteriza porque la cabeza queda posicionada hacia anterior respecto de los hombros en el plano sagital, se identifica por adoptar una cifosis torácica aumentada, debilidad de los músculos flexores profundos del cuello, romboides y serrato anterior y contracturas de los músculos pectorales mayor y menor, trapecio superior y elevador de la escapula (Khosravi et al, 2019). Existen distintos métodos de medición para la anteposición de cabeza y cuello, la más aceptada es la medición del ángulo craneovertebral (Mani et al, 2017).…”
Section: Introductionunclassified
“…The existing studies on face detection and recognition mainly tackles two issues: extraction of facial features, and statistics and comparison of facial images. Many features are taken as the bases for judgement, including facial contour, skin color, and texture [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%